Incidence, prevalence and risk factors for low back pain in adolescent athletes: a systematic review and meta-analysis - Wilson, Fiona; Mockler, David (My University, 2022)
Objective To investigate the incidence, prevalence, risk factors and morphological presentations of low back pain (LBP) in adolescent athletes. Design Systematic review with meta-analysis. Data sources Medline, Embase, CINAHL via EBSCO, Web of Science, Scopus. Eligibility criteria for selecting studies Studies evaluating the incidence and/or prevalence of LBP in adolescent athletes across all sports. Results There were 80 studies included. The pooled incidence estimate of LBP in adolescent athletes was 11% (95% CI 8% to 13%, I2=0%) for 2 years, 36.0% (95% CI 4% to 68%, I2=99.3%) for 12 months and 14% (95% CI 7% to 22%, I2=76%) for 6 months incidence estimates. The pooled prevalence estimate of LBP in adolescent athletes was 42% (95% CI 29% to 55%, I2=96.6%) for last 12 months, 46% (95% CI 41.0% to 52%, I2=56%) for last 3 months and 16% (95% CI 9% to 23%, I2=98.3%) for point prevalence. Potential risk factors were sport participation, sport volume/intensity, concurrent lower extremity pain, overweight/high body mass index, older adolescent age, female sex and family history of LBP. The most common morphology reported was spondylolysis. Methodological quality was deemed high in 73% of cross-sectional studies and in 30% of cohort studies. Common reasons for downgrading at quality assessment were use of non-validated survey instruments and imprecision or absence of LBP definition. Summary/conclusion LBP is common among adolescent athletes, although incidence and prevalence vary considerably due to differences in study methodology, definitions of LBP and data collection.
PUBLISHED
Keywords: adolescent athlete; low back pain; sport; LOW BACK PAIN